Odpowiedzi

  • zntt
  • Początkujący
2010-01-05T23:03:45+01:00
B ) 4y + x = -2
4yx - 2 / : 4yx
yx = 2

3x - 8y = 10
3x + 8y = 10
11xy - 10 / : 11xy
xy = 1,1

2010-01-05T23:03:55+01:00
A) { x + 4y=2
3x - 8y= 10
x= - 4y +2
3 (-4y + 2) - 8y = 10
12y+ 6 - 8y = 10
4y= 10 - 6
4y = 4 / : 4
y = 1
x + 4 = 2
x= 4 - 2
{x= 2
{y = 1

reszte robisz tak samo. Podstawiasz x do drugiego równania ;d
2010-01-05T23:07:28+01:00
B)
[x=-2-4y
[3(-2-4y)-8y=10

[x=-2-4y
[-6-12y-8y=10

[x=-2-4y
[-20y=16

[x=-2-4y
[y=-0,4

[x=-2-4(-0,4)
[y=-0,4

[x=-2+1,6
[y=-0,4

[x=-0,4
[y=-0,4

c)


[x=3+2y
[-2(3+2y)+y=0

[x=3+2y
[-6-4y+y=0

[x=3+2y
[-3y=6

[x=3+2y
[y=-2

[x=3+2(-2)
[y=-2

[x=3-4
[y=-2

[x=-1
[y=-2

d)
[y=9-2x
[5x-36+8x=3

[y=9-2x
[13x=39

[y=9-2x
[x=3

[y=9-6
[x=3

[y=3
[x=3